PENGARUH ESG DISCLOSURE TERHADAP FIRM VALUE DENGAN MEDIA EXPOSURE SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Perusahaan sektor Energy di Indonesia yang Tercatat di Bursa Efek Indonesia tahun 2021 – 2024) - Agustin Rismawati; Wahyu Meiranto (Diponegoro Journal of Accounting, 2026)
Increasing attention to environmental, social, and governance ESG issues is encouraging companies to disclose desired information as a form of transparency to stakeholders. However, extent of ESG disclosure does not necessarily increase firm value if investors do not consider the information relevant. This study aims to analyze the effect of ESG disclosure on firm value, with media exposure as a mediating variable. This study employs a quantitative approach using secondary data obtained from Bloomberg and national media coverage of companies in the energy sector listed on the Indonesia Stock Exchange (IDX) during the period 2021 – 2024. The sampling size of 60 observations. Data analysis was conducted using panel data regression and the Sobel test to examine the mediating role of media exposure.The results indicate that ESG disclosure has a significant positive effect on media exposure but a significant negative effect on firm value. Meanwhile, media exposure has non-significant positive effect on firm value. Furthermore, media exposure is also unable to mediate the effect of ESG disclosure on firm value. These result indicate that ESG disclosure can increase media attention due to its informational value for stakeholders. However, this information has not been able to increase firm value because investors still prioritize financial information and view ESG disclosure as a cost. Furthermore, companies have not optimally utilized media as a communication tool. Overall, this study highlights that the influence of ESG disclosure on firm value is still influenced by investor perceptions and the effectiveness of the compant’s media.